'Victim': What Is Hidden behind This Word?. (24th November 2015) - Lacerda, Tessa
Abstract: People affected by the Brazilian civil–military dictatorship (1964–1985) often resist acknowledging their own victimhood. This essay looks into possible reasons for this reluctance to self-identify as a victim. Towards that end, a philosophical analysis of what is known as 'scapegoat theory' is undertaken. According to this theory, victims must be regarded as absolutely blameless, thus being defined exclusively as objects upon which violence is perpetrated. Consequently, victims do not recognize themselves as either subjects or free political agents, ones able to demand their rights within the public sphere. In this sense, to revisit the theme of human rights and how it relates to democracy may clear a potential path for reflection on what an actual 'victim' might be.